Optimum Basic Seedling Density and Yield and Quality Characteristics of Unmanned Aerial Seeding Rice - Haibin Zhu; Xizhan Lu; Kaiwei Zhang; Zhipeng Xing; Haiyan Wei; Qun Hu; Hongcheng Zhang (Agronomy, 2023)
Unmanned aerial seeding (UAS) is an efficient unmanned rice planting method with broad application prospects. But its optimum basic seedling number and yield and quality characteristics remain unclear. Field experiments were conducted to compare UAS, unmanned dry direct seeding (UDDS), and unmanned carpet transplanting (UCT) methods using inbred japonica rice variety Nanjing 5718. The UAS method was subdivided into four planting density treatments (UAS105, UAS150, UAS195, and UAS240 = 105, 150, 195, and 240 seedlings/m2, respectively). The results showed that increasing the basic seedling density first increased the yield but then it decreased, and UAS195 produced a significantly higher yield. On the other hand, the grain processing, appearance, and taste quality deteriorated with improved nutritional quality. Among the three planting methods, UAS (UAS195) yielded less than UCT due to there being fewer spikelets per panicle, a lower grain-filling rate, and less photosynthetic activity after heading. However, UAS (UAS195) produced more yields than UDDS by having more panicles, more spikelets per panicle, and more biomass accumulation. Both UAS195 and UDDS had poorer grain processing, appearance, and nutritional quality than UCT, but increased amylose content and taste values. Therefore, UAS195 could be an alternative planting method for inbred japonica rice with coordinated yield, quality, and production efficiency.